Changing gender practices among the Tiv of Central Nigeria from pre-colonial to post-colonial period - Nyajoh, Evelyn; Ahoo, Terhile Jude; Oragbai , Josephine; Kete , Tartor Titus (Journal of Contemporary International Relations and Diplomacy, 2026)
This study investigates the transformation of gender practices among the Tiv of Central Nigeria from the pre-colonial to the post-colonial period. It arose from the contradiction between the Tiv’s historic gender complementarity and the deepening patriarchal control of modern times. The objectives were to examine pre-colonial gender balance, analyse the colonial disruption of traditional relations, explore post-colonial socio-moral transformations that re-inscribed patriarchy, and assess emerging forms of female agency shaping Tiv society’s gendered future. The Feminist Theory of Intersectionality provided the analytical framework, offering a lens to examine how gender, culture, economy, and religion intersect to shape women’s positions and experiences in Tiv over time. A qualitative historical-descriptive design was employed, drawing data from ethnographic records, colonial archives, oral traditions, and contemporary scholarship. Information was thematically analysed to identify continuities and changes in gender roles, power relations, and social organization. Findings reveal that pre-colonial Tiv society emphasised gender complementarity and communal welfare through institutions like Yamshe (Exchange Marriage). Colonial intrusion abolished these stabilising systems, introducing Kem (cash-based bride price), commodifying marriage and labour, and intensifying male dominance. Post-colonial developments, marked by moral regulation, religious influence, and economic inequality further entrenched patriarchy, especially in matters of sexuality and reproduction. Yet, Tiv women exhibit “bounded agency,” seen in cultural performance, education, and subtle defiance of restrictive norms. The study concludes that Tiv society remains in transition, balancing patriarchal continuity with emergent gender change. Culturally informed education and reform are recommended to promote a more inclusive gender order